The sequence $\{u_{n}\}$, $\{v_{n}\}$ is defined by $$u_{0} =u_{1} =1,u_{n}=2u_{n-1}-3u_{n-2}(n\geq2)$$ $$v_{0} =a, v_{1} =b , v_{2}=c,v_{n}=v_{n-1}-3v_{n-2}+27v_{n-3} (n\geq3)$$ .There exists the positive integer $N$ such that when $n> N$ ,have $u_{n}\big|v_{n}$ . Prove that $$3a=2b+c$$

I have do following $$u_n=\dfrac{\left (1+i\sqrt{2}\right )^n+\left (1-i\sqrt{2}\right )^n}{2}$$ $$v_n=\alpha\cdot 3^n+\beta \cdot \left (-1-2i\sqrt{2} \right )^n+\gamma \cdot \left (-1+2i\sqrt{2} \right )^n$$

I think basics method does not works here.

Any ideas ?


Notice that if you write $p,q = 1 \pm \sqrt {-2}$ the characteristic roots of the first linear recurrence, the characteristic roots of the second are their products, $p^2,pq=3$, and $q^2$.
So an easy way to make a sequence satisfying the second one that also satisfies the divisibility condition is to multiply $u_n$ with another integer sequence satisfying the first one. In essence, this exercise shows that this is the only way to make them.

Some linear algebra with a sprinkle of Galois theory shows that the $\Bbb Q$-vector spaces of rational sequences that are solutions to those recurrence have dimension $2$ and $3$, generated over $\Bbb Q$ by $\{(p^n+q^n) ; \sqrt{-2}(p^n - q^n)\}$ for the first one and by $\{(p^{2n}+q^{2n}) ; (pq)^n = 3^n; \sqrt{-2}(p^{2n} - q^{2n})\}$ for the second one, and all those sequences are integer sequences.

From this we get that $u_n = \frac 12 (p^n + q^n)$ and there are rational numbers $x,y,z$ such that $v_n = x(p^{2n} + q^{2n}) + y(pq)^n + z\sqrt{-2}(p^{2n}-q^{2n})$.
We can scale $v_n$ by an nonzero integer without strengthening the hypothesis nor weakening the goal we need to prove, so we can assume that $x,y,z$ are integers to make things easier.

Then, if $u_n$ divides $v_n$ then it also divides $v_n - (p^n+q^n)(x(p^n+q^n)+z\sqrt{-2}(p^n-q^n)) = (y-2x)(pq)^n = (y-2x)3^n$.
Moreover, a quick induction shows that $3$ never divides $u_n$, and so $u_n$ divides $y-2x$ for all $n$.

Since $u_n$ is unbounded, we must have $y = 2x$. Then, $v_n = 2u_n (x(p^n+q^n)+z\sqrt{-2}(p^n-q^n))$, which implies that the sequence $v_n/u_n$ satisfies the same linear recurrence as $u_n$.

In particular, since the first three values of $u_n$ are $1,1,-1$ and the first three values of $v_n$ are $a,b,c$, the first three values of $v_n/u_n$ are $a,b,-c$, and thus $-c = 2b-3a$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.